Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Другие варианты решения
Раздел:

Номер №120

Выполните умножение:
а)
$(3a - 15b) * \frac{8}{a^2 - 25b^2}$
;
б)
$(x^2 - 4) * \frac{2x}{(x + 2)^2}$
;
в)
$\frac{y}{3y^2 - 12} * (y^2 - 4y + 4)$
;
г)
$\frac{2ab}{a^2 - 6ab + 9b^2} * (a^2 - 9b^2)$
.

Решение а

$(3a - 15b) * \frac{8}{a^2 - 25b^2} = 3(a - 5b) * \frac{8}{(a - 5b)(a + 5b)} = 3 * \frac{8}{a + 5b} = \frac{24}{a + 5b}$

Решение б

$(x^2 - 4) * \frac{2x}{(x + 2)^2} = (x - 2)(x + 2) * \frac{2x}{(x + 2)^2} = \frac{2x(x - 2)}{x + 2}$

Решение в

$\frac{y}{3y^2 - 12} * (y^2 - 4y + 4) = \frac{y}{3(y^2 - 4)} * (y - 2)^2 = \frac{y}{3(y - 2)(y + 2)} * (y - 2)^2 = \frac{y}{3(y + 2)} * (y - 2) = \frac{y(y - 2)}{3(y + 2)}$

Решение г

$\frac{2ab}{a^2 - 6ab + 9b^2} * (a^2 - 9b^2) = \frac{2ab}{(a - 3b)^2} * (a - 3b)(a + 3b) = \frac{2ab}{a - 3b} * (a + 3b) = \frac{2ab(a + 3b)}{a - 3b}$
Другие варианты решения